The Herald and Daily News’ framing of the leaked Zimbabwean draft constitution and Vice President Joice Mujuru’s fall from grace - Chibuwe, Albert (International Journal of Communication, 2020)
Debates in Zimbabwe give the impression that mass media are central to the country’s democratization. Focusing on two seemingly unrelated but defining events in Zimbabwe’s political life—the framing of the leaked draft constitution (January–February 2012) and Vice President Joice Mujuru’s fall from grace (August 2014–June 2015)—this article investigates whether the concern about the media’s role in Zimbabwe’s democratic project is justified. A comparative analysis of Daily News and The Herald was carried out to ascertain how the two newspapers framed the two events and to judge the extent to which they can be said to be informative and educative. Content analysis of the two publications and in-depth interviews with The Herald news editor and a senior reporter and with Daily News’ news editor and political editor were used to establish their perceptions regarding their newspapers’ framing of the two events. The article reveals that the two publications’ framing of the events was polarized and did not assist citizens to make informed decisions. The Herald was pro-Mugabe, while Daily News was anti-Mugabe.